Combining single nucleotide polymorphisms and gene expression of LEP, FABP4, STAT5A and DGAT1 genes for improvement of body weight in Holstein calves - Mostafa, RM; Elgamal, RM; Khadra, NH; Helal, NG; Khedr, NM; El-Sherbeny, GA; Safhi, FA; Sakr, SA; Ateya, AI (Journal of the Hellenic Veterinary Medical Society, 2024)
The objective of this study was to investigate the possible association of single nucleotide polymorphisms and gene expression of leptin (LEP), fatty acid binding protein (FABP4), signal transducer and activator of transcription 5A (STAT5A) and diacylglycerol acyltransferase (DGAT1) genes with body weight in Holstein calves. For the RNA extraction process, blood samples from 100 Holstein bull calves were taken. According to farm records, the acquired bull calves were weaned at a body weight of roughly 90 kg, with birth weights ranging from 31 to 38 kg and weaning ages ranging from 60 to 100 days. To account for the non-genetic causes, the dairy calves’ body weight was changed to their 205-day body weight. Nucleotide sequence changes in the form of SNPs were found in the LEP, FABP4, STAT5A, and DGAT1 genes in the investigated Holstein calves. The identified SNPs and corrected 205-day body weight showed a significant correlation (P < 0.05). According to ΔCT values, a significant relationship between the mRNA levels of the LEP, FABP4, STAT5A, and DGAT1 genes and body weight was also found (P < 0.05). The effectiveness of the LEP, FABP4, STAT5A, and DGAT1 genes as proxies for growth qualities in Holstein dairy calves is highlighted by this study. Therefore, it was possible to select an animal with a high rate of growth.